Integration of project-based learning to improve scientific process skills and conceptual understanding in the learning process of invertebrate zoology - A. Abas; Mohamad Amin; I. Ibrohim; Sri Endah Indriwati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Further analysis of the effectiveness of integrating project-based learning (PjBL) in Invertebrate Zoology courses to improve students' science process skills and conceptual understanding needs to be carried out. This research was aimed to analyze the integration of PjBL in the Invertebrate Zoology course on scientific process skills and conceptual understanding of student. As for seeing the effect of each indicator from each predictor, a qualitative descriptive analysis was carried out. Respondents in this study were students of the Biology Education Study Program FTTE Universitas Bengkulu. A sample of 30 respondents was taken by random sampling technique. The research instrument is a questionnaire for scientific process skills and tests for understanding concepts. The hypothesis is tested using Analysis of Variance (ANOVA). The integration of PjBL has a significant influence on the scientific skills process of 0.038 with an F value of 4.524 and also has a significant influence on concept understanding at 0.018 with an F value of 0.018. It was concluded that there was an effect of the integration of PjBL on scientific process skills and conceptual understanding of Invertebrate Zoology, with a significance level of 0.05, so that it can be taken into consideration in developing learning in the Invertebrate Zoology course.